Evaluation of synergistic antiplaque activity of Salvadora Persica L. and Camellia Sinensis Var. Assamica: A comparative clinical study / Hayder Raad Abdulbaqi - Hayder Raad, Abdulbaqi (2017)
Green tea, non-fermented leaves of Camellia sinensis var. assamica, is widely consumed as healthy beverage since thousands of years in Asian countries. Chewing sticks (miswak) of Salvadora persica L. are traditionally used as natural toothbrush to ensure oral health in developing countries. Both green tea and Salvadora persica L. extracts were reported to have antibacterial activity against many dental plaque bacteria. However, their combination has never been tested to have antibacterial and antiadherence effects against primary dental plaque colonizers, playing an initial role in the dental plaque development, which was investigated in this study. Thus, the aim of this study was to evaluate the synergistic antiplaque activity of the combination of green tea and Salvadora persica L. aqueous extracts both in vitro and in vivo. In the in vitro part of the study, two-fold serial micro-dilution method was used to measure minimal inhibitory concentration (MIC) of aqueous extracts of green tea, Salvadora persica L. and their combinations. Adsorption to hexadecane was used to determine the cell surface hydrophobicity (CSH) of bacterial cells. Glass beads were used to mimic the hard tissue surfaces, and were coated with saliva to develop experimental pellicle for the adhesion of the primary colonizing bacteria. While in the in vivo part of the study, a double-blinded, randomized, 24 hours plaque re-growth crossover clinical trial was carried out involving 14 participants who rinsed with test (combination of green tea and Salvadora persica L. aqueous extracts), 0.12% chlorhexidine (CHX) and placebo mouth rinses for 24 hours. A week before the trial, all participants received scaling, polishing and oral hygiene instruction. On the trial day, the participants received polishing at base line and rinsed with 15 ml of randomly allocated mouth rinse twice a day without oral hygiene measures. After 24 hours, plaque index was scored and then the participants entered a six days washout period with usual oral hygiene measures after which they repeated the same protocol for the following two mouth rinses. In vitro results have revealed that green tea aqueous extracts exhibited better antiplaque effect than Salvadora persica L. aqueous extracts. Their combination, equivalent to 1/4 and 1/2 of MIC values of green tea and Salvadora persica L. aqueous extracts respectively, showed synergistic antiplaque properties with fractional inhibitory concentration (FIC) equal to 0.75. This combination was found to significantly reduce CSH (p < 0.05) and lower the adherence ability (p < 0.003) towards experimental pellicle. In vivo, significant differences were found between mouth rinses by means of plaque index. Test mouth rinse significantly reduced plaque accumulation when compared with placebo and CHX mouth rinses. CHX mouth rinse non-significantly reduced plaque accumulation when compared with placebo. In conclusion, combination between green tea and Salvadora persica L. aqueous extracts exhibited synergistic antiplaque activity against primary dental plaque colonizers in vitro. Rinsing with 15 ml of this combination twice daily has a significant antiplaque effect better than CHX for a 24 hours period in vivo; therefore it could be utilized as a natural alternative mouth rinse to CHX.